Transatlantic voices : interpretations of Native North American literatures - Pulitano, Elvira, 1970- (Book collections on Project MUSE., 2007)
A collection of critical essays by European scholars on contemporary Native North American literatures. Devoted to the primary genres of Native literature - fiction, nonfiction, drama, poetry - these essays chart the course of theories of Native literature, and delineate the crosscurrents in the history of Native literature studies.